Students’ perceptions towards the challenging factors in online distance learning - Mohamad, Faizah; Ramlan, Zarina Suriya; Anuarsham, Afiqah Humaira; Abdul Kadir, Zaemah; Darmi, Ramiza (Human Resource Management Academic Research Society, 2022)
Since the COVID-19 outbreak, the learning environment in higher learning institutions has now transformed from the traditional face-to face to online distance learning (ODL). This transformation will undoubtedly pose some challenges for the students. Therefore, it is important to identify these challenges so that measures can be made to support students’ learning in the new norm. Using the TIPEC (Technology, Individual, Pedagogy, and Enabling Conditions) framework, this research aims at identifying the most challenging factor in ODL as perceived by the students and to examine the influence of gender as well as fields of study on the factors. Employing a quantitative research method, an 18 item-questionnaire was developed based on TIPEC framework and distributed to students in a public university via online. 60 students responded to the survey and the data gathered were analysed using both descriptive and inferential statistics. . The means were used to describe the students’ perceptions on the challenges they faced in ODL. Meanwhile, t-Test and One-Way ANOVA were run to see the differences in the perceptions based on gender and fields of study respectively. The major findings revealed that students perceived the individual factor as the most challenging factor and the pedagogy factor was the least in ODL. It was also discovered that gender influenced the individual and technological factors, but fields of study had no influence on any of the factors. It is important to note that the findings can help students, lecturers and administrators of higher learning institutions understand the challenges in ODL so that they can take actions to ensure successful teaching and learning in this new norm. Future researches should explore other aspects such as the students’ support system and coping strategies in ODL.